A new strategy for synthesis of porous magnetic supraparticles with excellent biodegradability. Issue 10 (22nd December 2014) - Li, Dian; Zhang, Yuting; Yu, Meng; An, Qiao; Guo, Jia; Lu, Jennifer Q.; Wang, Changchun
Abstract : Porous biodegradable magnetic supraparticles with surface area up to 285.4 m 2 g −1 have been fabricated by a one-step etching method. Abstract : Porous magnetic supraparticles (p-MSPs) with surface area up to 285.4 m 2 g −1 have been fabricated by a one-step etching method, which is 4 times greater than the unetched counterpart. They exhibit significantly better biodegradability than their counterpart in both mimicked physiological buffer solution and the cellular environment of HeLa cells.